2009
DOI: 10.1002/ange.200904360
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on the Reaction between R2N‐NONOates and Aquacobalamin: Evidence for Direct Transfer of a Nitroxyl Group from R2N‐NONOates to Cobalt(III) Centers

Abstract: Unglaubliche Geschichten: Das Übertragen einer Nitroxylgruppe von R2N‐NONOaten auf Aquacobalamin, bei dem Nitroxylcobalamin entsteht, verläuft nicht über eine H+‐katalysierte R2N‐NONOat‐Zersetzung, sondern wahrscheinlich über ein NONOat‐Cobalamin‐Intermediat (siehe Schema; r.d.s.=geschwindigkeitsbestimmender Schritt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
(41 reference statements)
1
10
0
2
Order By: Relevance
“…In animals living at high elevations and in low-oxygen environments, the NADH dehydrogenase complex was found to be under positive selection in residue substitutions (Yu et al 2011). This was thought to interfere with metabolic performance (Hassanin et al 2009). In this study, we only investigated nad2 gene expression in mussels responding to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In animals living at high elevations and in low-oxygen environments, the NADH dehydrogenase complex was found to be under positive selection in residue substitutions (Yu et al 2011). This was thought to interfere with metabolic performance (Hassanin et al 2009). In this study, we only investigated nad2 gene expression in mussels responding to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…[7] DETAN ONOate (NONOate) decomposes by hydrolysis at acidic pH, releasing two NO molecules. [8] CPT-11, ac amptothecin derivative,h as been utilized to treat various cancers,including breast cancer; nevertheless,this molecule suffers from Pgp-induced efflux. [9] Figure 1d epicts the structure/composition of this HM carrier system and the mechanism by which it treats CPT-11resistant breast cancer cells (MCF-7/ADR) that are generated subcutaneously in anude mouse model.…”
mentioning
confidence: 99%
“…To prevent hydrolysis,NONOate is typically stored in an alkaline buffer at pH 8.0. [8] Figure 2a shows photomicrographs of the resultant HMs following the evaporation of dichloromethane.T he HMs were monodisperse with ap olydispersity of about 3%,a nd had ad iameter of 387.1 AE 11.7 mma nd as hell thickness of 24.5 AE 2.4 mm( n = 6b atches). TheN ONOate (48.5 AE 1.2 mgmg À1 )a nd CPT-11 (3.2 AE 0.5 mgmg À1 )c ontents in HMs were determined by UV/Vis absorption spectroscopy after the HMs had been broken by sonication.…”
mentioning
confidence: 99%
“…[5] Difficulties in this reduction are related to mutations of the corresponding MMACHC genes, [4] and medical studies suggest some therapeutic effect for Cbl derivatives that are easier to reduce than 1 to the intermediate Co II state. [6,7] Detailed studies have been reported for the inorganic chemistry of Cbls with different ligands at the b side (upper side), [8][9][10] but rather little is known how structural changes at the a side (lower side) of the molecule influence the coordination behavior of the Dmbz base [11][12][13] and the corresponding redox properties of the metal ion. Herein, we report on the coordination chemistry and accompanying electrochemical properties of a new class of vitamin B 12 mimics in which a peptide linker tethers the corrin macrocycle to the Dmbz base.…”
mentioning
confidence: 99%